DESENVOLVIMENTO DE UMA FERRAMENTA COMPUTACIONAL PARA ANÁLISE DE FLUXOS TÉRMICOS EM EDIFICAÇÕES - Leitzke, Rodrigo; Freitas, Julye; Cunha, Eduardo Grala da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The building thermal balance is fundamental for the evaluation of the building thermoenergetic performance. I defined by the heat gains and losses balance considering the external environment. Computational simulation is an important tool capable of performing these analyzes, such as EnergyPlus software, performing simulations involving thermal and energy issues and being able to simulate at different time steps. One of the results analysis methods of a computational simulation is the elaboration of thermal flows. This analysis involves a series of variables providing an evaluation of what is most influential in the thermal balance observing the building envelope are related in graphs that separate the relations of losses and gains. The objective of this work is to present the implementation of a tool that automates the generation of thermal flows, representing graphically the numerical results obtained through computational simulations in EnergyPlus. The method was divided into three stages, technology analysis, code development and application of the tool in an existing model. The results show the feasibility of implementing this tool for computational simulations in EnergyPlus.